Draft Genome Sequence of Romboutsia weinsteinii sp. nov. Strain CCRI-19649(T) Isolated from Surface Water - Maheux, Andrée F. (Genome Announc, 2017)
Romboutsia weinsteinii sp. nov. CCRI-19649(T) belongs to the genus Romboutsia. The strain was isolated from a water sample harvested in Québec City, Québec, Canada. The genome assembly comprised 4,134,593 bp with a 29.3% GC content. This is the first documentation that reports the genome sequence of R. weinsteinii.